2013
DOI: 10.1128/aac.02541-12
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific and Drug-Specific Differences in Susceptibility of Candida Biofilms to Echinocandins: Characterization of Less Common Bloodstream Isolates

Abstract: e Candida species other than Candida albicans are increasingly recognized as causes of biofilm-associated infections. This is a comprehensive study that compared the in vitro activities of all three echinocandins against biofilms formed by different common and infrequently identified Candida isolates. We determined the activities of anidulafungin (ANID), caspofungin (CAS), and micafungin (MFG) against planktonic cells and biofilms of bloodstream isolates of C. albicans (15 strains), Candida parapsilosis (6 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
27
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 64 publications
3
27
0
1
Order By: Relevance
“…With the exception of the planktonic MIC of ANID for C. guilliermondii that was six 2-fold dilutions (64-fold) higher than the corresponding MIC for C. albicans M61, the MICs of all four antifungal agents against planktonic cells of the Candida species studied displayed good in vitro activity with comparable susceptibility profiles (Table 1, 0.06 to 1 mg/liter), as also previously documented by us and others (13,14,18,19). However, mature biofilms of C. lusitaniae and C. guilliermondii showed higher MICs to the three echinocandins than their corresponding planktonic cells ( Table 1; P Ͻ 0.01).…”
supporting
confidence: 63%
See 3 more Smart Citations
“…With the exception of the planktonic MIC of ANID for C. guilliermondii that was six 2-fold dilutions (64-fold) higher than the corresponding MIC for C. albicans M61, the MICs of all four antifungal agents against planktonic cells of the Candida species studied displayed good in vitro activity with comparable susceptibility profiles (Table 1, 0.06 to 1 mg/liter), as also previously documented by us and others (13,14,18,19). However, mature biofilms of C. lusitaniae and C. guilliermondii showed higher MICs to the three echinocandins than their corresponding planktonic cells ( Table 1; P Ͻ 0.01).…”
supporting
confidence: 63%
“…While Candida biofilms are generally recalcitrant to conventional antifungal agents, liposomal amphotericin B and echinocandins have demonstrated good antibiofilm activities which are both species and drug specific (10)(11)(12)(13)(14). Candida lusitaniae and Candida guilliermondii are known to have relatively high MICs to echinocandins (10,13,14) that may create greater challenges in eradication of their biofilms from vascular catheters (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vitro and in vivo models designed to assess the antifungal susceptibility of Candida biofilms (19,21,(23)(24)(25)(26)(27)(28)(29) showed that the echinocandins, particularly micafungin, had the highest antifungal activities (30)(31)(32)(33)(34). However, the studies are limited by the inclusion of a low number of clinical isolates; furthermore, the concentration of antifungal necessary to inactivate sessile cells is unknown.…”
mentioning
confidence: 99%